Pelaksanaan Tradisi Batimbang Tando dalam Walimah Perkawinan di Nagari Salareh Aia Perspektif Fikih Munakahat - Nisa Wati; Endri Yenti (Lembaga Yasin AlSys, 2026)
Minangkabau customary marriage traditions have been widely studied, but research specifically examining the implications of the classification of tando gadang and tando kaciak for the organization of wedding feasts from the perspective of fiqh al-munakahat remains limited. This study aimed to analyze the implementation of the batimbang tando tradition in Nagari Salareh Aia and examine its status and implications for the organization of wedding feasts from the perspective of fiqh al-munakahat. The study employed a qualitative approach with a case study design through field research. Informants were selected using purposive sampling and included niniak mamak, alim ulama, community leaders, bundo kanduang, and community members involved in the implementation of the batimbang tando tradition. Data were collected through observation, in-depth interviews, and documentation and were subsequently analyzed using the interactive analysis model of Miles, Huberman, and Saldaña through the stages of data condensation, data display, and conclusion drawing and verification. The results showed that batimbang tando functions as a customary mechanism that regulates marriage agreements, strengthens interfamily relationships, and maintains social order within the community. The distinction between tando gadang and tando kaciak has implications for the form of wedding feast arrangements but does not indicate differences in family social status. From the perspective of fiqh al-munakahat, this tradition can be categorized as ‘urf sahih because it does not conflict with Sharia principles and contains values of public benefit. These findings strengthen scholarship on the relationship between custom and Islamic law and affirm that local traditions can be maintained as long as they are consistent with religious values. In practical terms, the results can serve as a reference for the community in preserving the batimbang tando tradition without disregarding the principles of fiqh al-munakahat. Future research should examine variations in batimbang tando practices in other Minangkabau regions using a comparative approach.